(untitled) (Research, Society and Development, 2022)
Vitamin D plays an important role in immunity and its deficiency or insufficiency (hypovitaminosis D) may be related to the increased prevalence of autoimmune diseases. In a retrospective cohort study with single samples, drawn from a public hospital database, the vitamin D profile of a population was verified. A total of 2,977 patients from 127 municipalities in Pernambuco, Brazil participated in the study. In 12.6% of the municipalities normal means of vitamin D were found (D≥30ng/ml) and in 65.6% deficient means (D<20ng/mL). Recife exposed the largest number of inhabitants with vitamin D deficiency (321) and presented 100% of the female sample (n=650) with hypovitaminosis D (D<30ng/ml). Vitamin D deficiency (D≤20ng/mL) in this municipality was identified in 20.3% of the sample and insufficiency (D≥20ng/mL<30ng/mL) in 79.7%. In the cities surrounding Recife, the average of vitamin D deficiency was 13.3% and that of insufficiency was 86.7%. Regarding the involvement of hypovitaminosis D with autoimmune diseases, the study articles highlighted the association of hypovitaminosis D with the risk of autoimmune diseases. Regarding the prevalence of hypovitaminosis D in autoimmune diseases, 93.0% of the articles agreed with this association. Regarding the influence of hypovitaminosis D on the activity of the autoimmune disease, 63.6% recognized this association. The predominance of hypovitaminosis D is getting worse, mainly in the female population and regardless of age. Since hypovitaminosis D is a risk factor for autoimmune diseases, it is important to develop strategies for its prevention, especially in this population.